HPLC-MS/MS-based metabolic profiling and pharmacological properties of extracts and infusion obtained from Amelanchier parviflora var. dentata - DOĞAN, AHMET; EMRE, GİZEM (ELSEVIER SCIENCE BV, 2018)
Arnelanchierparviflora var. dentata is an endemic medicinal plant traditionally consumed to treat stomach pain, cardiovascular diseases, and urinary tract infections in Turkey's folk medicine. Although Amelanchier genus is an excellent source of phytochemicals with a panoply of biological activities, no report has been made available on Amelanchier parviflora var. dentata. Thus, the metabolic profiles of methanol, ethyl acetate, and water extracts were obtained using HPLC-MS/MS. Besides, the pharmacological properties such as antioxidant activity and enzyme inhibition effects against acetyl/butyrylcholinesterase, tyrosinase, alpha-amylase, and alpha-glucosidase were evaluated. In total, 62, 38, and 16 metabolites were Identified from the methanolic, water, and ethyl acetate extracts, respectively. The identified metabolites belong to anthocyanins, phenolic acids, and flavonoids. The tested extracts exhibited different enzyme inhibitory activity against cholinesterases (acetylcholinesterase: 0.52-2.47 mg GEs/g extract and butyrylcholinesterase: 0.47-3.59 mg GEs/g extract), tyrosinase (19,0-145.54 mg KAEs/g extract), alpha-amylase (0.23-1.10 mmol ACEs/g extract), and alpha-glucosidase (8.89-9.92 mmol ACEs/ g extract). Evidence from the present study supports the necessity for more research in an endeavor to discover biologically active secondary metabolites from A. parviflora to manage specific ailments.
Keywords: Amelanchier parviflora; Antioxidants; Chemical fingerprints; Enzyme inhibitors; Phenolics; Anthocyanins; ANTIOXIDANT ACTIVITY; ALPHA-GLUCOSIDASE; ALNIFOLIA NUTT.; PHENOLIC-COMPOUNDS; PLANTS; BERRIES; TURKEY; ACID; ACETYLCHOLINESTERASE; ANTICHOLINESTERASE